The Contribution of the Western World to the Islamic Economy in Indonesia - Hisam Ahyani; Memet Slamet; Naeli Mutmainah (UIN Siber Syekh Nurjati Cirebon, 2021)
Islamic economics that is applied in various countries, including Islamic banking or in Indonesia is called Sharia Banking. This study wants to reveal how the western world's response to Islamic economics is?; and what is the contribution of the western world to the Islamic economy in Indonesia?. This type of research is a normative juridical research with the nature of this research is a descriptive legal study. This study is intended to explore the response of the western world to the Islamic economy that exists in Indonesia. This study produced findings, namely: First, the western world's response to the Islamic economy, namely the Western economic system is intended to embrace the Islamic economic system and support the existence of the Islamic economic system itself, as a result, the western world applies a free business system based on capitalism which prioritizes capital for development. economy in the Islamic world. Second, the contribution of the western world to the economy in Indonesia is a necessity which incidentally is not an Islamic State. However, in its scope, Islamic law in Indonesia in this case the sharia economy is subject to the national economic system, although in Indonesia itself the sharia economic system and conventional economics in Indonesia have their own legal umbrella. So that the Islamic economic system in Indonesia until now is an alternative concept for a prosperous economic system in Indonesia, one of which is a capitalist economic system. Islamic law, especially the Qur'an and al-Hadith. The implication of the western response to the existence of a sharia economy in Indonesia is a golden opportunity for Indonesia to develop a sharia economy, one of which is the halal industry, halal tourism (religion), sharia economic brand, money waqf, the potential of the halal industry sector in Indonesia can be developed through halal food ( halal food), halal fashion, halal cosmetics, and so on, this means that economic freedom in Indonesia needs to be developed. In addition, halal tourism can also be developed in Indonesia, with various potentials that exist in Indonesia. Another implication related to the western response to the Islamic economy in Indonesia is the presence of a diversity of halal food. However, the development of this potential needs to make the resulting production must be based on the principles of benefit and justice, where this benefit is carried out by prioritizing sharia economics as a real need where justice is very meaningful in the economy, especially in Indonesia.Â